TINJAUAN HUKUM TERHADAP PENINGKATAN PELAYANAN PASPOR RI DI ERA DIGITAL PADA KANTOR IMIGRASI KELAS I A TPI (TEMPAT PEMERIKSAAN IMIGRASI) SAMARINDA - Agustina, Agustina (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACT This study discusses the legal review of how to improve passport services and efforts to improve passport services in the digital era at the Immigration Office Class I TPI (Immigration Checkpoint) Samarinda. As explicitly stated in Law Number 6 of 2011 concerning Immigration, a passport is one of the travel documents issued by the Government of the Republic of Indonesia which is intended for Indonesian citizens who wish to travel abroad, therefore, the Class I Immigration Office TPI (Immigration Checkpoint) Samarinda as one of the technical implementing units under the Directorate General of Immigration of the Ministry of Law and Human Rights of the Republic of Indonesia continues to innovate and improve passport services for the community. Through the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 08 of 2014 concerning Ordinary Passports and Travel Letters Like Passports, it shows that the provisions related to Indonesian passport services for the community have been implemented properly by the Immigration Office Class I TPI (Immigration Checkpoint) Samarinda, therefore growth in the quality and quantity of Indonesian Passport services at the Immigration Office Class I TPI (Immigration Checkpoint) Samarinda continues to increase in line with the duties and functions of the Immigration Office in general as well as the efforts made by the Immigration Office Class I TPI (Immigration Checkpoint) Samarinda in improving passport services Indonesia in the current digital era goes through 3 steps, including the Eazy Passport Service, SIMPATIK Passport Service and M-Passport Service, the three forms of services that have been provided by the Immigration Office Class I TPI (Immigration Checkpoint) Samarinda of course in line with the policy direction of using digital technology. which of course aims to realizing the effectiveness and efficiency of Indonesian passport services to the public Keywords: Immigration, Service, Passport